Monetary trends and business cycles in Denmark 1875-2005: New evidence using the framework of financial accounts for organising historical financial statistics - Kim Abildgren (Danmarks Nationalbank, 2006)
The paper constructs financial-account stock data for Denmark 1875-2005 on an annual frequency and explores the historical monetary and financial trends and cycles on the basis of the new data set. The annual financial-account data constructed in the paper are based on a comprehensive range of historical financial statistics. The data set presented is broken down by 8 institutional sectors (central bank; commercial banks and savings banks; mortgage-credit institutes; lifeinsurance companies and pension funds; investment associations; central government; other residents; non-residents) and 6 main types of financial instruments (gold and SDR; currency; loans and deposits; bonds, shares and mutual funds shares; insurance technical reserves; capital and reserves). Commercial banks, savings banks and mortgage-credit institutions played a significant credit-supplying role in the Danish economy already during the late 19th century and in the beginning of the twentieth century. A turning point emerged during the early 1930s, and by the middle of the 1950s the ratio of credit to GDP had declined substantially. Since then the trend has reversed but the pre-World War I level was not reached until the decade from the mid-1970s to the mid-1980s. To some extent real asset prices have displayed a similar pattern. There has been a massive growth in the assets under management by life-insurance companies and pension funds since the mid-1970s and by collective investment funds since the mid-1990s. There has been a much stronger positive correlation between money and prices at the longterm frequencies (8-40 years cycles) than at the business cycle frequency (2-8 years), but in the post-World War II period prices seem to have led money at all frequencies. In the period 1875-1945 house prices led credit from mortgage-credit institutions with a considerable leadtime (6 years) in the long-term cycles - in the post World War II period the lead-time has been considerable shorter (1 year). During the whole period 1875-2005 real credit granted by banks and mortgage-credit institutions have been almost contemporaneous with real GDP, and the largest correlation coefficients have occurred in the long-term cycles. The overall conclusion in the paper is that financial accounts are a useful framework for organising and analysing financial data even when data sources are somewhat fragmented and sparse, which is often the case in relation to historical financial statistics. Financial accounts can be useful in an attempt to paint a more coherent picture of the historical development of the financial system and the financial structure. Utilising accounting identities a system of financial accounts allows e.g. for the compilation of the net financial asset position of the non-financial private sector, even when no separate balance-sheet statistics covers this sector. To date projects related to historical national-accounts have - both in Denmark and internationally - only focused on the real side of the economy. It would, however, be interesting if future projects would make an attempt to cover long-span time series of financial accounts as well, including both stock- and flow-data.
Keywords: C82; E3; G00; N23; N24; 330; financial accounts; historical financial statistics; financial sector development; financial markets history; monetary transmission; cycles; band-pass filters; Finanzmarkt; Geldvermögen; Geldpolitik; Konjunktur; Dänemark